2010
DOI: 10.1111/j.1471-4159.2010.06613.x
|View full text |Cite
|
Sign up to set email alerts
|

Signaling, delivery and age as emerging issues in the benefit/risk ratio outcome of tPA For treatment of CNS ischemic disorders

Abstract: Abbreviations used: BBB, blood-brain barrier; ERK, extracellular signal related kinase; ET, endothelin; FPI, fluid percussion brain injury; ICH, intracerebral hemorrhage; JNK, c-Jun-N-terminal kinase; LRP, low-density receptor-related protein; MAPK, mitogen-activated protein kinase; MMP, matrix metalloproteinase; NVU, neurovascular unit; PA, plasminogen activator; PAI-1, PA inhibitor I; RBC, red blood cells; TBI, traumatic brain injury; tPA, tissue-type plasminogen activator; uPA, urokinase plasminogen activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 89 publications
(215 reference statements)
0
27
0
Order By: Relevance
“…Tissue-type plasminogen activator (tPA) remains the only FDA-approved treatment for acute ischemic stroke, because intravenous thrombolysis with tPA is an approved and effective therapy for acute ischemic stroke within the first 3 h from onset (Armstead et al, 2010). However, cerebral edema is an uncommon but potentially lethal complication postintravenous thrombolysis in addition to the risk of cerebral hemorrhage (Cruz-Flores et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Tissue-type plasminogen activator (tPA) remains the only FDA-approved treatment for acute ischemic stroke, because intravenous thrombolysis with tPA is an approved and effective therapy for acute ischemic stroke within the first 3 h from onset (Armstead et al, 2010). However, cerebral edema is an uncommon but potentially lethal complication postintravenous thrombolysis in addition to the risk of cerebral hemorrhage (Cruz-Flores et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In general, treadmill exercise is commonly applied to stroke patients thanks to its beneficial effect on neuroprotection11, 12 ) . To date, the only therapy approved by FDA has been thrombolytic tissue plasminogen activator (tPA) although approximately 80% of human strokes are classified into ischemic stroke13,14,15 ) . It is suggested that continuous researches via experimental ischemic stroke models should be performed to develop novel, proper, and helpful solutions for patients with ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the mechanisms underlying stroke include oxidative stress, blood-brain barrier dysfunction, neuronal apoptosis and inflammation (5,6). Although tissue-type plasminogen activator is used clinically and remains the only FDA-approved treatment for ischemic stroke, it is not so effective for all patients and only a small number of patients recover as a result of the reperfusion injury and a narrow 3 h time-window for safe administration (7). Therefore, other effective therapeutic agents are required to assist the patients with their diseases.…”
Section: Introductionmentioning
confidence: 99%